2021
DOI: 10.18011/bioeng2021v15n4p660-671
|View full text |Cite
|
Sign up to set email alerts
|

Germinação De Sementes De Plantas Daninhas Submetidas Ao Teste De Envelhecimento Acelerado

Abstract: O estudo teve como objetivo analisar o efeito do envelhecimento acelerado sobre a germinação de sementes de plantas daninhas. O experimento foi conduzido em laboratório, com delineamento inteiramente casualizado em esquema fatorial 4x5, sendo sementes quatro espécies (capim-carrapicho ( C. echinatus ), capim-colchão ( D. horizontalis ), caruru ( A. viridis ) e corda-de viola ( I. grandifolia)) cinco períodos de envelhecimento (0, 24, 36, 48 e 72 horas), e cinco repetições. As sementes foram envelhecidas à temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Wang et al (2017) reported that the best temperatures for germination in the species Digitaria sanguinalis were between 25 and 35 ºC. Wenneck et al (2021) subjected Amaranthus viridis seeds to accelerated aging at a constant temperature of 42 °C and obtained a reduced germination potential of the seeds compared with those that were not subjected to this treatment.…”
Section: Second Experimentsmentioning
confidence: 99%
“…Wang et al (2017) reported that the best temperatures for germination in the species Digitaria sanguinalis were between 25 and 35 ºC. Wenneck et al (2021) subjected Amaranthus viridis seeds to accelerated aging at a constant temperature of 42 °C and obtained a reduced germination potential of the seeds compared with those that were not subjected to this treatment.…”
Section: Second Experimentsmentioning
confidence: 99%